The Effects of Religiosity and Halal Knowledge on the Decision to Use the Covid-19 Vaccine - Nabila Nurrahmi; Reny Fitriana Kaban; Hidayat Sofyan Widjaja (Ilomata International Journal of Social Science, 2023)
This study intends to investigate how religious affiliation and knowledge on halal practices affect the decision to take the Covid-19 vaccination. The variables tested in this research consisted of the independent variables namely religiosity and halal knowledge whereas the dependent variable is the decision to use the Covid-19 vaccine. The purposive sampling method was implemented, with the sample of 100 Muslims aged over 12 who had been given the Covid-19 vaccination in Jakarta. The PLS analysis approach was used to analyze the data obtained. Based on the findings, the following conclusions are generated as follows: (1) Religiosity has a positive and significant impact on the decision to use a vaccine product; (2) the perspective on halal practices has a positive and significant impact on the choice of vaccine product; and (3) both religiosity and halal knowledge simultaneously have a positive and significant impact on the choice to use a product. This study recommends that every company manufacturing the Covid-19 vaccines imposes halal elements in the process. The halal label in the Covid 19 vaccine is crucial because in communities where strong levels of religiosity prevails, consumers consider a halal status in goods consumption is of a high value. Recommendations are proposed for the public to investigate further about the halalness of the Covid-19 vaccine through continuous socialization to ensure that the vaccine is safer and more effective.